Bacteria Fight Back, Also in Indonesia! - Pratiwi Sudarmono (Acta Medica Indonesiana)
Get an infection, take an antibiotic. That simple, sensible, and often life-saving intervention, repeated myriad times, has triggered an ever-escalating war between humans and microbes—a war the microbes seem to be winning. Almost as soon as penicillin was introduced in 1942, bacteria started to develop resistance. Now, many common bacteria have acquired resistance to multiple antibiotics, making some infections extraordinarily difficult to treat. Antibiotic resistance is the ability of a microorganism to withstand the effects of an antibiotic. In Indonesia, antibiotics can be purchased even without a doctor’s prescription. Now, as bacterial resistance to antibiotic are increasing, the potency of an antibiotic to eradicate pathogenic bacteria seems to be decreasing, not very long after a new antibiotic is available in the market. Generally, the development of resistant bacteria to antibiotics happen spontaneously or because of a pressure of inappropriate antibiotic use in clinical practice. In Indonesia, the absence of antibiotic regulation to be used in human as well as animal health is also believed to have contributed to the rapidly increasing incidence of multidrug resistant bacteria. The antibiotic resistant bacteria has become a serious problem especially for patients hospitalized in intensive care units. More than 40% of the budget for drugs is allocated for antibiotics, and once the causative bacteria develops resistance to antibiotics, the case fatality rate of the infections increases.